Furāș at-Tafā’ul ‘Inda Ta’allumi al-Lughah aś-Śāniyah fī Qō’ati ad-Dars - Himmatul Mahmudah (University of Darussalam Gontor, 2017)
Abstract There is a common belief that learning a second language involves learning rules as especially learning the correct vocabulary and pronunciation. The development of these laws in all contexts is a natural extension of grammar. Assume that the use of language is not different in the position of the first language than in the positions of multiple languages. All those required to speak a second language successfully has to activate correct formulas which is to say the same thing as well as what native speakers said in his/her language. We often find such conditions while in the process of language learning in the classroom which is the main driving force in learning the second language the learners are exposed to. Furthermore, one of the key to success in learning a second language is the ability to absorb (assimilation). The form of language learning process in the classroom is the concept which allows the native speakers to assess and understand the pronunciation of non-native speakers and vice versa. This program provides opportunities for interaction in the classroom and attention of all learners to the events of language learning which makes the process of second language acquisition runs successfully especially for the learners of non-native speakers.Keywords: learn the second language, the classroom, entrance, language acquisitionفرص التفاعل عند تعلم اللغة الثانية في قاعة الدرسبقلم: همة المحمودةجامعة مالانج الحكومية ملخصهناك اعتقاد شائع بأن تعلم الغة الثانية يتضمن تعلم قواعد نحو اللغة الثانية، بالإضافة إلى تعلم المفردات والقواعد الصحيحة للنطق. ويعد وضع هذه القوانين قيد الاستعمال في جميع السياق امتدادا طبيعيا لاكتساب النحو. تفترض أن استعمال اللغة لا يختلف في موقف اللغة الأولى عنه في مواقف اللغات الثانية المتعددة. فكل ما هو مطلوب للتحدث بلغة ثانية الناجح هو تفعيل الصيغ الصحيحة لتقول الشيئ نفسه الذي يقوله المرء في لغته الأصلية. ونجد بمثل هذه الظروف عند عملية تعلم اللغة في قاعة الدرس. حيث كانت القوة الرئيسية المحركة في تعلم اللغة هي اللغة التي يتعرض لها المتعلمون. وتعدّ القدرة على الاستيعاب سمة من سمات نجاح تعلم اللغة الثانية، ويشكل تعلم اللغة في قاعة الدرس هذه المفهومية/ الاستيعاب بأن يقدر المتكلم الأصلي على فهم نطق المتكلم غير الأصلييين وبالعكس. توفير فرص التفاعل في قاعة الدرس واهتمام بما جرى فيها من الأحداث اللغوية سيتم عملية تعلم اللغة الثانية بنجاح مبين، ولاسيما للمتعلمين غير الناطقين بتلك اللغات. ويكون الاهتمام إلى اللغة في قاعة الدرس بإمعان النظر، ومعالجة المدخل لممارسة الذاكرة وإتقان التدريس على شكل الاكتساب ثم التركيز على الصيغة داخل قاعة الدرس تمكن الوصول إلى فرادة التعليمات عند تعلم اللغة الثانية.الكلمات الرئيسية: تعلم اللغة الثانية، قاعة الدرس، المدخل، الاكتساب.